WPŁYW NOWYCH KODYFIKACJI KARNYCH NA USTAWĘ O PRAWIE AUTORSKIM I PRAWACH POKREWNYCH - Gerecka-Żołyńska, Anna (Wydział Prawa i Administracji UAM, 1999)
The main criminal rules included in intellectual property law are discussed in the paper and, then, the necessity of their changes is shown. The comparison of the new penal code acts to those of intellectual property law - which indicates reiteration of some of them - is presented. The necessity of prosecution forms’ modification is also shown in the paper. Presently, in most of the cases accusations acts are brought into the court by a victim, but - when considering the nature of the offences - they should be prosecuted by the police or public prosecutor. As it was shown - the implementation of the new penal procedure institution, namely of mediation, can be very beneficial for the legal system. It was pointed out that many legal acts must however be modified in order to harmonize Polish legal system with European Union regulations.
THE IMPACT OF A NEW PENAL LEGISLATION ON INTELLECTUAL PROPERTY LAW